PEMBELAJARAN TEKS BIOGRAFI SULTAN HAMID II BERDASARKAN K13 SISWA KELAS X MAN 1 PONTIANAK - Putri, Tri Febriyanti; Syambasril, Syambasril; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine whether the teacher has implemented the biography text learning well in accordance with the rules of curriculum 2013. The method used in this research is descriptive method in qualitative form. This research decribing the plans, the implements, and the result of the learning biographical text which implemented by the teacher to the students at Grade X MAN 1 Kota Pontianak, the data sources in this research is Indonesia Language subject teacher and students in MAN 1 Kota Pontianak. The data in this research results from observation APKG 1 and AKPG 2 and the result of the students. Based on the analysis, done it could conclude that planning that has been made by the teacher is good, although in making indicators and purposes there was a mistake. Implementing learning carried out by the teacher is appropriate to the planning although there was a component which not delivered while implement the learning. Evaluation of learning that has been arranged by the teacher is good, although the attitude assessment was not carried out. The suggestion intended for Indonesia language teachers to make learning more interesting and using media which tedious.Key Words: Biographical Text, Learning, Sultan Hamid II